Combined Malonic and Methylmalonic Aciduria Due to ACSF3 Variants Results in Benign Clinical Course in Three Chinese Patients - Wang, Ping; Shu, Jianbo; Gu, Chunyu; Yu, Xiaoli; Zheng, Jie; Zhang, Chunhua; Cai, Chunquan (Frontiers in Pediatrics, 2021)
Introduction: Combined malonic and methylmalonic aciduria (CMAMMA) is a rare metabolic disease caused by biallelic variants in ACSF3 gene. The clinical phenotype is highly heterogeneous in this disorder, ranging from asymptomatic to severe symptoms. No cases with CMAMMA was reported in China. Materials and Methods: In this study, three Chinese pediatric patients were diagnosed with CMAMMA unexpectedly while being treated for other ailments. To better characterize CMAMMA in Chinese population, we made a multidimensional analysis with detailed clinical phenotype, semi quantitative detection of urine organic acid and analysis of ACSF3 gene variants. Results: The clinical presentation of these patients is quite different, their main complaints were anemia, jaundice or abnormal urine test respectively. They showed no symbols of the classic methylmalonic academia, but urine organic acid analysis showed elevated malonic acid and methylmalonic acid in all the patients repeatedly. Variants were found at 4 sites in ACSF3 gene. Patient 1 carried the compound heterogeneous variant c.689G>A (p.Trp230*)/c.1456G>A (p.Ala486Thr). A compound heterozygous variant c.473C>T (p.Pro158Leu)/c.1456G>A (p.Ala486Thr) was identified in patient 2. Patient 3 harbored a novel homozygous variant c.1447A>G (p.Lys483Glu). Conclusions: Three Chinese patients were diagnosed with CMAMMA caused by ACSF3 variants. Their clinical course revealed that CMAMMA can be a benign condition that doesn’t affect individual growth and development, but severe clinical phenotype may appear when other triggers exist. This study systematically elaborates CMAMMA in Chinese population for the first time, broadens the spectrum of gene variant and provides a strong basis for the etiological study of this disorder.